A systematic review of methods for reducing embodied energy in building materials: a quantitative cradle-to-gate analysis - Kautsar, Reihan Hafizah; Larasati, Dewi; Suhendri, Suhendri (Universitas Mercu Buana, 2025)
Reducing embodied energy (EE) in building materials is a critical aspect of achieving sustainable building construction. Embodied energy refers to the total energy consumed in the extraction, processing, transportation, and manufacturing of building materials before they reach the construction site. In conventional buildings, total energy consumption is predominantly influenced by operational energy (OE), which includes energy used for heating, cooling, lighting, and ventilation throughout the building’s lifespan. However, in energy-efficient buildings, the proportion of EE to total energy demand becomes more significant, sometimes equaling or surpassing OE. This shift highlights the growing importance of minimizing EE in sustainable building design. This study conducts a systematic review using the PRISMA framework, extracting relevant data from the Scopus database to categorize methods for reducing EE within cradle-to-gate systems. These methods are classified into three phases: the material phase, the construction method phase, and the design phase. The material phase includes three approaches: mixed material intervention, production process intervention, and material substitution. The construction method phase encompasses two approaches: building component substitution and process or method substitution. Finally, the design phase focuses on interventions at the building design level. Despite these classifications, the findings suggest that no single phase or approach demonstrates a significantly greater impact on EE reduction than the others. Each approach contributes comparably to reducing EE, highlighting that while notable progress has been made, the relative effectiveness of individual methods remains consistent across phases. Integrated approaches combining strategies across multiple phases hold promise for substantial reductions in EE, emphasizing the need for future research to refine and innovate these methodologies.